2020
DOI: 10.1101/2020.08.31.275909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AKT1 mediates multiple phosphorylation events that functionally promote HSF1 activation

Abstract: The heat stress response activates the transcription factor heat shock factor 1 (HSF1), which subsequently upregulates heat shock proteins to maintain the integrity of the proteome. HSF1 activity requires nuclear localization, trimerization, DNA binding, phosphorylation, and gene transactivation. Phosphorylation at S326 is an important regulator of HSF1 transcriptional activity. Phosphorylation at S326 is mediated by AKT1, mTOR, p38, and MEK1. mTOR, p38, and MEK1 all phosphorylated S326 but AKT1 was the more p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
(160 reference statements)
0
1
0
Order By: Relevance
“…In breast cancer, HSF1 can be overexpressed with 10-15% of patients having HSF1 gene amplification (17). In addition, HSF1 can be hyperactivated stemming from increased proteotoxic stress and hyperactivation of activating kinases including AKT1, mTORC1, and p38 among others (21)(22)(23)(24)(25). A seminal finding describing the function of HSF1 in cancer identified that HSF1 has a unique transcriptional program in cancer cells, distinct from the heat stress response transcriptional program, that indicated HSF1 has several additional functions in cancer (26).…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, HSF1 can be overexpressed with 10-15% of patients having HSF1 gene amplification (17). In addition, HSF1 can be hyperactivated stemming from increased proteotoxic stress and hyperactivation of activating kinases including AKT1, mTORC1, and p38 among others (21)(22)(23)(24)(25). A seminal finding describing the function of HSF1 in cancer identified that HSF1 has a unique transcriptional program in cancer cells, distinct from the heat stress response transcriptional program, that indicated HSF1 has several additional functions in cancer (26).…”
Section: Introductionmentioning
confidence: 99%